(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
What is the role of media in today’s India? It is thequestion which may have a number of answers. Whatever the answers, however,they are all of vital importance and anybody can guess it with ease. In Indiawe have associated with media a large number of hopes, aspersions,apprehensions, liabilities, challenges. We cannot see the future without anactive, fair and strengthened media. This, however, is not possible withoutputting in heavy investment in this industry. Taking in view the complexitiesand king of technologies that media involve, it has been recommended at timesthat the substantial growth cannot be achieved in media without foreigninvestments. On the other hand, there are people who have been opposing themove and raising the burning issues like national security and socialresponsibility etc. Therefore, the way of foreign investment has not been easyin Indian media industry. This paper intends to find out the developments onthis issue.